Termination of Algebraic Rewriting with Inhibitors - Bottoni, Paolo; Hoffmann, Kathrin; Parisi Presicce, Francesco (Electronic Communications of the EASST, 2006)
We proceed with the study of termination properties in the double pushout approach to algebraic rewriting, and show a concrete termination criterion for rewriting systems with inhibitors. Inhibitors prevent elements in an algebra toparticipate in rule matches, so that termination depends only on whether new possibilities for matches are created. The notion of inhibitor can be extended to consideringdifferent levels of inhibition, by which the ability of an element to participate in a match is progressively reduced. We illustrate the approach by considering someapplication contexts in model transformation.